Intracorneal Ring Segments Followed by Simultaneous Topography-Guided Removal of Epithelium and Stroma With Accelerated Collagen Cross-Linking For Keratoconus (I-TRESK/CXL). Issue 2 (March 2021) - Shetty, Rohit; Israni, Neeraj Ashok; Ramuka, Saurabh; Dadachanji, Zelda; Roy, Abhijit Sinha; Mehra, Rohan; Lalgudi, Vaitheeswaran Ganesan
Abstract : Purpose: The aim of this study was to assess the visual, topographic, and aberrometric outcomes of a novel tissue sparing technique, topography-guided removal of epithelium, and stroma in keratoconus (TRESK) along with accelerated collagen cross-linking (CXL), 1 month after Intacs insertion. Design: Prospective interventional study. Methods: Fourty-eight eyes (45 patients) with keratoconus underwent femto-assisted Intacs insertion. After 1 month, TRESK and CXL (9 mW/cm 2 for 10 minutes) was done. TRESK is a decentered trans-PTK (phototherapeutic keratectomy) with center and area of ablation at the location of the steepest tangential anterior curvature and area of the cone respectively. Total ablation (epithelium plus stroma) was limited to 75 μm. Postoperative measurements were performed 1 month after Intacs, 6 weeks after Intacs followed by TRESK/CXL, and at the final visit 12 months after Intacs followed by TRESK/CXL. Results: For all eyes studied, uncorrected distance visual acuity and corrected distance visual acuity (CDVA) (logMAR) improved from preoperative means of 1.05 ± 0.05 and 0.31 ± 0.03 logMAR to postoperative means of 0.52 ± 0.05 ( P < 0.001) and 0.20 ± 0.02 logMAR ( P = 0.009), respectively. The mean preoperative sphere, cylinder and mean refractive spherical equivalent decreased from −4.52 ± 0.98 D, −4.81 ± 0.25 D, −6.93 ± 0.99 D to −0.77 ± 0.53 D ( P = 0.029), −3.13 ± 0.24 D ( P = 0.002), and −2.34 ± 0.53 D ( P = 0.021), respectively with a mean keratometric flattening of 5.06D ( P < .0001) at the final visit. In total, 2.08% of the eyes lost 1 Snellen line of CDVA. Sixty eight percent and 27% of the eyes gained 2 Snellen lines or more of uncorrected distance visual acuity and CDVA, respectively. Conclusions: Simultaneous TRESK with CXL done 1 month after Intacs insertion (I-TRESK) in keratoconus eyes provided significant visual gain with refractive and topographic improvement. This novel procedure involving customized PTK before CXL is safe, easy to plan and perform, and provides good outcomes.